2019
DOI: 10.3171/2019.3.spine1999
|View full text |Cite
|
Sign up to set email alerts
|

Centers for Medicare & Medicaid Services Hierarchical Condition Category score as a predictor of readmission and reoperation following elective inpatient spine surgery

Abstract: OBJECTIVEA universal, objective predictor of postoperative resource utilization following inpatient spine surgery has not been clearly established. The Centers for Medicare & Medicaid Services (CMS) Hierarchical Condition Category (HCC) risk adjustment model, based on a formula using patient demographics and coded diagnoses, is currently used to prospectively estimate financial risk in Medicare Advantage patients; however, the value of this score as a clinical too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“… 32 - 34 The first step toward improving the value is identifying populations at risk for increased utilization of these resources. In a previous study at our institution, 35 patients with increased comorbidity burden were found to have higher rates of 30-day readmissions after lumbar fusion, in alignment with multiple other studies. 36 , 37 Beyond overall comorbidity burden, increased age, female sex, preoperative levels of pain and function, socioeconomic factors, and a variety of individual comorbidities, including depression and anxiety, diabetes, congestive heart failure, chronic obstructive pulmonary disease, and obesity, have all been linked with increased resource utilization and cost of care after lumbar fusion.…”
Section: Discussionsupporting
confidence: 88%
“… 32 - 34 The first step toward improving the value is identifying populations at risk for increased utilization of these resources. In a previous study at our institution, 35 patients with increased comorbidity burden were found to have higher rates of 30-day readmissions after lumbar fusion, in alignment with multiple other studies. 36 , 37 Beyond overall comorbidity burden, increased age, female sex, preoperative levels of pain and function, socioeconomic factors, and a variety of individual comorbidities, including depression and anxiety, diabetes, congestive heart failure, chronic obstructive pulmonary disease, and obesity, have all been linked with increased resource utilization and cost of care after lumbar fusion.…”
Section: Discussionsupporting
confidence: 88%
“…They found that there was a significant association between the HCC score and readmission rates, length of stay, need for reoperation, and cost. [24] Notably Medicaid and commercial insurers is important. It's well documented that treatment at a center with high case volume is associated with better outcomes and lower complications rate which in turn lead to lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…Turcot et al recently published a report where they tested this model on patients that underwent different spinal surgical interventions. They found that there was a significant association between the HCC score and readmission rates, length of stay, need for reoperation, and cost [21].…”
Section: Discussionmentioning
confidence: 99%